ANALISIS FAKTOR-FAKTOR PENGHAMBAT TRANSFORMASI DIGITAL DAN PERKEMBANGAN EKONOMI DESA WISATA BERBASIS TEKNOLOGI PADA DESA DI KECAMATAN AJIBATA - Junaidi Junaidi; Eve Ida Malau (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
Ajibata District is a tourist area in North Sumatra. This sub-district has 9 villages and 1 kelurahan. From the results of the initial survey, researchers found the fact that each village has its own potential and wealth, but is not managed optimally. This can be seen from 90% of the management of MSMEs, IKM, Cooperatives, BUMDes, Farmers Groups, and other economic activities that are still manual and have no touch of technology. The purpose of this study was to analyze the inhibiting factors for the transformation and economic development of technology-based tourism villages. If the factors that cause delays in technology entering the village economic system are known, this will make it easier for the government to design and run programs related to improving the village economy. To achieve this goal, the researcher plans the stages of the research to be carried out, namely the first step the researcher conducts an initial survey and literature study to further sharpen the researcher's understanding of the problem to be studied specifically. Then the researchers collected the necessary data and information either through observation, interviews, and questionnaires. The collected data is then tested for validity and validity before being analyzed further to determine conclusions. The results of this study are partially X1, X2, X5, and X6 variables have no significant effect on Digital Transformation. Variables X3 and X4 have a significant effect on Digital Transformation. Simultaneously the variables X1, X2, X3, X4, X5, and X6 together have a significant effect on Digital Transformation (Y).